Views and Experiences of Adults who are Overweight and Obese on the Barriers and Facilitators to Weight Loss in Southeast Brazil: A Qualitative Study. Issue 1 (1st January 2020) - Morgan, Caroline; de Wildt, Gilles; Prado, Renata Billion Ruiz; Thanikachalam, Nisha; Virmond, Marcos; Riley, Ruth
ABSTRACT: Background : Obesity in Brazil is increasing with 54% of the Brazilian population being overweight, of which 20% is obese. Obesity is a risk factor for non-communicable diseases such as cardiovascular disease: the leading cause of mortality in Brazil. This study aims to identify the barriers and facilitators to weight loss as perceived by patients with a view to reducing the burden of obesity-related diseases on patients and healthcare services. Methods : Fifteen qualitative, semi-structured, in-depth interviews were conducted in the preventive medicine department in a private health clinic in Bauru, Southeast Brazil. Inductive thematic analysis was conducted. Results : The barriers and facilitators were classified into three themes: lifestyle, motivation and education. Barriers include cost of a healthy lifestyle, time management, personal safety, mobility, junk food advertising, sustaining weight loss, mental health, lack of support and health education. Facilitators include change in eating habits, sleep quality, cooperative food networks, access to the multidisciplinary team and expert patients as health educators. Conclusion : Expert patients should be utilized as an education method, as they increase motivation, promote the facilitators and provide realistic expectations of the weight loss process. Barriers such as junk food advertising and accessibility to treatment need to be addressed. Abbreviations : BMI: Body Mass Index; NCD: Non-Communicable Disease; SUS: Sistema Único de Saúde; WHO: World Health Organization